Implementasi Pendidikan Karakter Melalui Pembiasaan Peringatan Hari Besar Islam Pada Peserta Didik di SD Negeri Bumi 1 Laweyan Surakarta - Sarafuddin Sarafuddin (Indonesian Journal Publisher, 2025)
This research aims to provide a clear picture of: (1) The strategy for implementing character education through the habituation of Islamic holiday observances among students at SDN Bumi 1 Laweyan Surakarta, and (2) The results of implementing character education through the habituation of Islamic holiday observances among students at SDN Bumi 1 Laweyan Surakarta. This research is a descriptive qualitative study, with a single embedded case study strategy. Data were obtained from: (1) Places and events, namely learning activities and extracurricular activities at SDN Bumi 1 Laweyan Surakarta. From this data source, information will be obtained about the implementation of character education through the habituation of commemorating Islamic holidays among students; (2) Documents, namely documents in the form of school work program books, extracurricular documents, and student qurban savings record books, and (3) Informants, consisting of the principal, teachers, and 4th and 5th-grade students of SDN Bumi 1 Laweyan Surakarta. To obtain data, the following methods were used: (1) Observation; (2) Document analysis; and (3) In-depth interviews. To obtain data validity, triangulation of data/sources and methods is conducted. Data analysis techniques are carried out collectively among the analysis components, namely data reduction, data presentation, and verification or conclusion drawing, with interactive data collection using a cyclical model. The mandatory output targets of this research are non-Scopus international journals, Sinta 3 accredited journals, while the additional output targets are teaching materials, intellectual property rights (IPR), and presentation of results at refanas. The result of the technology readiness level is at TRL 2, which involves capturing the formulation of concepts and the application of technology for instilling character education in students.